TRANSLATION AS A TEACHING STRATEGY: TEACHER’S PERCEPTIONS - Curcio, Carolina Hanna; Trebien, Heitor Augusto Colli; Marian, Jane (Caderno PAIC, 2022)
This paper aims to evaluate and discuss how translation is perceived and if it is used as a teaching strategy by foreign language (LE) teachers, with emphasis on the English language. Through Roman Jakobson’s (2013) theories on types of translation and Christiane Nord’s (2018) functionalist approach and teaching, linguistics and translation theories, an interconnection among different approaches was developed to construct the theoretical background and data analysis. Data collection was achieved through an open and closed question survey which involved respondents’ sociodemographic data, their perspectives and views on the use of translation in the language classroom. Generally, it was concluded that the educators use translation frequently when teaching. In approximately 10% of the analyzed cases, it is perceived as a negative strategy that affects the learning process; however, according to 90% of respondents, translation is seen as a positive strategy, especially as a facilitating learning resource for lower levels. To amplify the concepts of translation, Jakobson’s three types were highlighted: intralingual translation, interlingual and intersemiotic. These were considered within the teaching context in consonance with Nord’s functionalist approach, that considers translation as a natural and intuitive practice with a social purpose. Translation can therefore be used in different levels with different objectives according to each context.